Evaluating the potential use of a dairy industry residue to induce denitrification in polluted water bodies: A flow-through experiment. (1st September 2019) - Margalef-Marti, Rosanna; Carrey, Raúl; Soler, Albert; Otero, Neus
Abstract: Improving the effectiveness and economics of strategies to remediate groundwater nitrate pollution is a matter of concern. In this context, the addition of whey into aquifers could provide a feasible solution to attenuate nitrate contamination by inducing heterotrophic denitrification, while recycling an industry residue. Before its application, the efficacy of the treatment must be studied at laboratory-scale to optimize the application strategy in order to avoid the generation of harmful intermediate compounds. To do this, a flow-through denitrification experiment using whey as organic C source was performed, and different C/N ratios and injection periodicities were tested. The collected samples were analyzed to determine the chemical and isotopic composition of N and C compounds. The results proved that whey could promote denitrification. Nitrate was completely removed when using either a 3.0 or 2.0 C/N ratio. However, daily injection with C/N ratios from 1.25 to 1.5 seemed advantageous, since this strategy decreased nitrate concentration to values below the threshold for water consumption while avoiding nitrite accumulation and whey release with the outflow. The isotopic results confirmed that nitrate attenuation was due to denitrification and that the production of DIC was related to bacterial whey oxidation. Furthermore, the isotopic data suggested that when denitrification was not complete, the outflow could present a mix of denitrified and nondenitrified water. The calculated isotopic fractionation values ( ε 15 NNO3/N2 and ε 18 ONO3/N2 ) might be applied in the future to quantify the efficiency of the bioremediation treatments by whey application at field-scale. Highlights: Whey can be recycled to promote nitrate attenuation. Daily injection at a C/N ratio of 1.25–1.5 avoided whey release with the outflow. The δ 15 N and δ 18 O of NO3 − confirmed that denitrification caused the attenuation. The δ 13 C of DIC and DOC demonstrated the production of DIC from whey oxidation.